SAFETY PLAN AND CONTROL OF ARTIFICIAL INTELLIGENCE: INTEGRATING MAQȦȘID AL- SHARĪ’AH, HISBAH AND TASAWUR AS MECHANISM - Azrin Ibrahim; Siti Noor Mawar Abdul Rahman (Journal of Islamic, Social, Economics and Development, 2019)
Artificial Intelligence (AI) is a gist in the fourth wave of Industial Revolution. However,the impact of artificial intelligence cannot be studied yet because it belongs to future technology. However, many researchers in neuroscience, cognitive science and computer science begins to highlight the importance of having safety plan and control of AI. This issues is pertinent also to Islam since it involves one of basic principles in Maqȧșid al-Sharī’ah in term of protection of ‘aql, Hisbah and Tasawur. This paper is attempt made to show the link of AI, Maqȧșid al-Sharī’ah, Hisbah and Tasawur. Concept and idea of AI, Maqȧșid al- Sharī’ah, Hisbah and Tasawur are discussed first through document review of secondary data, hence this research adopted descriptive methodology using content analysis of the concept and idea discussed earlier. It is then to be integrated and fixed into the picture of overall discussion. The finding of this discussion is concluded with a conceptual framework of safety plan and control of AI through Islamic perspective.